TASK-BASED LANGUAGE TEACHING AS AN ENGLISH LEARNING METHOD FOR ROOM SERVICE AND RESERVATIONS EMPLOYEES: A CASE STUDY - Vivin Afini; Fitri Nurdianingsih; Ridayani; M. Bambang Purwanto (Language and Education Journal, 2025)
In the hospitality industry, English communication skills are essential in providing quality services, especially for interactions with international guests. However, many employees need help mastering vocabulary and speaking fluency, especially in work tasks such as reservations and room service. This study aims to evaluate the effectiveness of task-based language teaching (TBLT) in improving the communication skills of hotel employees and identify obstacles and solutions to its implementation. This study uses a qualitative approach with 20 Grand Duta Syariah Palembang hotel employees. The results showed a significant improvement in vocabulary and speaking skills and a positive response to the relevance of the TBLT method. Simulation-based strategies and gradual training overcame obstacles in task design and technology application. This research offers a new approach to developing language training in the hospitality industry by integrating authentic tasks into training. In conclusion, TBLT is practical and applicable to professional training needs